2005
DOI: 10.1385/bter:106:1:051
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Membrane Potential Is Reduced in Copper-Deficient C<SUB>2</SUB>C<SUB>12</SUB> Cells in the Absence of Apoptosis

Abstract: Mitochondrial membrane potential is reduced in copper-deficient rat hearts, but it is uncertain if this will lead to the onset of apoptosis. To determine if copper deficiency per se leads to apoptosis, C2C12 cells were made copper deficient by treatment with the copper chelator tetraethylenepentamine (TEPA). In TEPA-treated cells, the activity of Cu, Zn-superoxide dismutase and cytochrome-c oxidase decreased dramatically. The protein levels of nuclear-encoded subunits of the cytochromie-c oxidase decreased, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Other investigators also demonstrated a beneficial effect of copper supplementation on streptozotocin-diabetic mice preventing ␤-cell death and diabetes development (43). Copper deficiency has been shown to reduce COX activity in cardiac mitochondria of nondiabetic rats, associating copper insufficiency with disruption of mitochondrial architecture (8,28,32,33,52), impaired mitochondrial oxidative phosphorylation, and reduced mitochondrial respiration (2,4,19). The finding that mitochondrial dysfunction is a factor in the development of diabetes has been assigned higher importance in the last decade, since mitochondrial DNA mutations in humans and ␤-cell-specific deletions of mitochondrial genes in animal models have been shown to cause diabetes (35,42,44).…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators also demonstrated a beneficial effect of copper supplementation on streptozotocin-diabetic mice preventing ␤-cell death and diabetes development (43). Copper deficiency has been shown to reduce COX activity in cardiac mitochondria of nondiabetic rats, associating copper insufficiency with disruption of mitochondrial architecture (8,28,32,33,52), impaired mitochondrial oxidative phosphorylation, and reduced mitochondrial respiration (2,4,19). The finding that mitochondrial dysfunction is a factor in the development of diabetes has been assigned higher importance in the last decade, since mitochondrial DNA mutations in humans and ␤-cell-specific deletions of mitochondrial genes in animal models have been shown to cause diabetes (35,42,44).…”
Section: Discussionmentioning
confidence: 98%
“…Copper deprivation is known to reduce CIV activity (Dallman and Goodman, ; Medeiros and Wildman, ; Chen et al, 2002, ; Medeiros and Jennings, ), increase cellular ROS levels (Rossi et al, ; Arciello et al, ), and induce the formation of giant mitochondria (Dallman and Goodman, ; Goodman et al, ; Wakabayashi et al, ; Wakabayashi, ). Given this background, the aim of the current study was to understand the adaptive responses of mitochondria to mild copper deprivation in terms of OXPHOS remodeling, ETC function, and mitochondrial dynamics in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, complex IV serves as a metal sensor in the regulation of respiratory rates ( Desler et al, 2012 ). Supporting this mechanism, copper deficiency reduces the expression and activity of complex IV ( Dallman and Goodman 1970 ; Chen et al, 2002 ; Medeiros and Jennings 2002 ; Chen et al, 2005 ; Zeng et al, 2007 ; Ruiz et al, 2014 ), but not the other respiratory complexes ( Zeng et al, 2007 ; Bustos et al, 2013 ). Regarding copper overload, the current results showed an increase in complex IV protein expression ( Ruiz et al, 2016 ).…”
Section: Getting Copper Into Mitochondriamentioning
confidence: 99%